PERILAKU BERBAHASA LATAH PADA BINTANG TAMU CHANEL YOUTUBE QISS YOU TV : UYING NANANG ANDIS ADE (TRIO LATAH) - Tusoleha, Wilda Amelia; Aulia Salsta, Putri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study examines the Behavior of Talkative Language on Youtube Channel Guest Stars Qiss You TV: Uying Nanang Andis Ade (Trio Latah). The purpose of this study is to describe the types of talk and the factors that cause talk in Chanel Qiss You TV guest star artist: Uying Nanang Andis Ade (Trio Latah) which consists of environmental factors and also infectious factors. The approach used in this research is a qualitative approach and a type of descriptive research. The results of this research are: Referring to the talkative language behavior experienced by the interviewees, it includes 2 types of talkativeness, namely talkative colalia and talkative ecoproxia. Talkative behavior can be differentiated according to type, namely Colalia talkativeness and Ecoproxia talkativeness. And the factors causing the source (Trio Latah) on the Qiss You Tv YouTube channel account consist of environmental factors and infectious factors.